2013
DOI: 10.1016/j.jprot.2013.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Novel aspects of understanding molecular working mechanisms of salivary glands of worker honeybees (Apis mellifera) investigated by proteomics and phosphoproteomics

Abstract: This study comprehensively analyses the characteristic of the proteome and phosphoproteome of honeybee salivary glands (SGs) between normal and single-cohort honeybee colonies. The SGs need a wide spectrum of proteins to support their multifaceted functions and ensure normal social management of the colony. The cephalic SG triggers labor transition from in-hive work to foraging behavior via the regulation of juvenile hormone and ethyl oleate titer. The thoracic SG stronger expressed of proteins related to carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 79 publications
1
19
1
Order By: Relevance
“…The centrality of these five protein families are also consistent with the high representation in the post-embryonic development of other honey bee organs, such as the pupal head (60), brain (61), hemolymph (62), hypopharyngeal gland (63,64), and salivary gland (65).…”
Section: Ligustica) Embryos (Normalized By Gapdh) (A) Is Significantsupporting
confidence: 69%
“…The centrality of these five protein families are also consistent with the high representation in the post-embryonic development of other honey bee organs, such as the pupal head (60), brain (61), hemolymph (62), hypopharyngeal gland (63,64), and salivary gland (65).…”
Section: Ligustica) Embryos (Normalized By Gapdh) (A) Is Significantsupporting
confidence: 69%
“…36 The phosphorylation sites were assigned using Scaffold PTM (version 1.1.3; Proteome Software, Portland, OR, USA) on the basis of the Ascore algorithm. 46 Only a site confidence greater than 95% was considered to be a mapped phosphorylation site in RJ proteins.…”
Section: Database Search and Site Localizationmentioning
confidence: 99%
“…3). The proteins with differential expression were clustered into a heat map according to previous studies [36,37] (Fig. 4), which showed that most of the differences were between the MSG-A and the other two regions.…”
Section: Pairwise Comparison Of the Msg-a -M And -P Proteomesmentioning
confidence: 99%